NPL, LDR AND CAR ON ROA GO BUSINESS CONVENTION COMPANY CONTAINED IN BEI PERIOD 2014-2016 - Monica Astri Prastiwi; Lilis Sulistyani; Andri Octaviani (STIE AUB Surakarta, 2018)
The objective to be achieved in this research is to provide empirical evidence of the significance of the effect of Non Performing Loan, Loan To Deposit Ratio and Capital Adequancy Ratio to Return On Asset of conventional go public banking company in Indonesia Stock Exchange period 2014-2016.Population in this research is Conventional Banking Company in BEI period 2014-2016. Sampling method using purposive sampling method. Samples that meet the criteria are 20 banking companies. The data used in this research is secondary data. Data analysis techniques using classical assumption test and hypothesis testing consist of multiple linear analysis, t test and coefficient of determination. The result of hypothesis testing shows that Non Performing Loan has negative but not significant effect to Return On Asset, Loan To Deposit Ratio and Capital Adequancy Ratio have positive but not significant effect to Return On Asset on conventional banking company go public in BEI period 2014-2016. Coefficient Determination of the three independent variables on Return On Asset showed results of 0.6%, which means 99.4% influenced by other variables not described in this study.Keywords: Profitability, Non Performing Loans, Loan To Deposit Ratio, Capital Adequacy Ratio